دراسة تجريبية وحسابية لتحسين عامل أداء دارة تبريد انضغاطية باستخدام مزائج من وسائط التبريد - حسن, أيوب; حمود, علاء (Latakia University Journal -Engineering Sciences Series, 2017)
تهدف هذه الدراسة إلى البحث بإمكانية استخدام مزائج من وسائط التبريد كبديل لوسيط التبريد R134a في دارة تبريد انضغاطية اختبارية مصممة للعمل على شحنة مقدارها 100 g من وسيط التبريد R134a دون إجراء تغيير أو تعديل في الدارة. المزيج الجديد الذي تم تشكيله لا يسبب أي ضرر لطبقة الأوزون وآمن للاستخدام ويتكون من (R134a)، البروبان (R290)، البوتان (R600)، تم استخدام ثلاث نماذج مختلفة من المزيج وتم مقارنة معامل الأداء (COP) وخواص أخرى مع وسيط التبريد R134a عند نفس الشروط وعند درجات حرارة تبخير مختلفة. أظهرت النتائج بأن المزيج M40 يظهر زيادة في معامل الأداء (COP) بمقدار 7.77% وزيادة في التأثير التبريدي بمقدار 30% وانخفاض في درجة حرارة التصريف من الضاغط بمقدار 3.2% وذلك مقارنة مع R134a. تدعم الدراسة إمكانية استخدام المزائج في دارات وسائط التبريد المصممة للعمل مع وسائط تبريد أحادية بدون الحاجة إلى إجراء أي تغيير في الدارة كما أنها تدعم إمكانية استخدام وسائط تبريد ذات مميزات ترموديناميكية ممتازة وصديقة للبيئة مثل البروبان والبوتان ولكن هناك تحذيرات من استخدامها بسبب قابليتها للاشتعال.The aim of this study is investigate in using refrigerants mixtures as substitute to R134a in a testing compression refrigeration cycle designed to work with a mass of 100g of R134a without make changing or modification in the cycle. The new mixture that made it is ozone-friendly, safe for using and consists of R134a, propane R290, butane R600, we use three various types of this mixture and the coefficient of performance (COP) and other properties was compared with R134a on the same conditions and on different evaporation temperature. The results shows the refrigerant mixture (M40) has higher coefficient of performance (COP) than that of R134a by about 7.77% and increasing the refrigeration effect about 30% and decreasing the discharge temperature from compressor 3.2% compared with R134a. This study support possibility of using refrigerant mixtures in refrigeration cycle that designed to work with pure refrigerant (single component) without making any change in the cycle also it support the possibility of using refrigerant that have an excellent thermodynamic properties and environmentally friendly like Propane and butane but there are some warning from using it because their flaming.